2001
DOI: 10.1051/0004-6361:20010007
|View full text |Cite
|
Sign up to set email alerts
|

Elemental abundance analyses with DAO spectrograms

Abstract: Abstract. Elemental abundances analyses are performed for the Mercury-Manganese stars υ Her, φ Her, and HR 7018 consistent with previous studies of this series using spectrograms obtained with Reticon and CCD detectors. Comparisons of the first two analyses with those performed using coadded photographic plates show the general consistency of the derived elemental abundances. For υ Her and for φ Her, abundances were newly found for O, and for Al, V, Zn, and Ce, respectively. HR 7018 is discovered to be a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 43 publications
8
64
0
Order By: Relevance
“…The effective temperature and gravity were first estimated by using the Strömgren photometry and corrected for CP stars. This estimation presents average dispersions of ∼200 K and ∼0.2 dex for T eff and log g, respectively (Adelman & Rayle 2000;Netopil et al 2008). We estimate similar dispersion values for T eff and log g by achieving the excitation and ionization equilibrium.…”
Section: Abundance Analysessupporting
confidence: 64%
See 2 more Smart Citations
“…The effective temperature and gravity were first estimated by using the Strömgren photometry and corrected for CP stars. This estimation presents average dispersions of ∼200 K and ∼0.2 dex for T eff and log g, respectively (Adelman & Rayle 2000;Netopil et al 2008). We estimate similar dispersion values for T eff and log g by achieving the excitation and ionization equilibrium.…”
Section: Abundance Analysessupporting
confidence: 64%
“…Adelman & Rayle (2000) and Netopil et al (2008) derived T eff corrections for the Strömgren and other photometric systems, depending on the chemical peculiarity. For the case of HgMn stars, the T eff directly derived by Strömgren photometry is overestimated, so that a correction is neccessary (Adelman & Rayle 2000;Netopil et al 2008). We corrected the derived values of the HgMn star HD 23950 according to Adelman & Rayle (2000), who found a systematic difference between parameters derived from photometric and spectrophotometric techniques.…”
Section: Atmospheric Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Adelman et al (2002) reported the first spectrum variability in Tables 4-8 are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/447/685 this stellar class of Hg II λ3984 in α And A, a discovery whose implications are still just being explored (see, e.g., Kockukhov et al 2005). With results from many stars one can look at the dependences on stellar parameters and make comparisons with theoretical predictions (see, e.g., Adelman et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The HgMn star υ Her (HD 144206, HR 5982), spectral type B9 III (Cowley et al 1969), was analyzed by Adelman (1992, Paper X) with coadded photographic plates and by Adelman et al (2001) (Paper XXIV) with S/N ≥ 200 Reticon and CCD spectrograms. υ Her is an example of an Fe and Ni-poor HgMn star.…”
Section: Introductionmentioning
confidence: 99%